Impact of DNA damage repair alterations on prostate cancer progression and metastasis - Lukashchuk, Natalia; Barnicle, Alan; Adelman, Carrie A.; Armenia, Joshua; Kang, Jinyu; Barrett, J. Carl; Harrington, Elizabeth A. (Frontiers in Oncology, 2023)
Prostate cancer is among the most common diseases worldwide. Despite recent progress with treatments, patients with advanced prostate cancer have poor outcomes and there is a high unmet need in this population. Understanding molecular determinants underlying prostate cancer and the aggressive phenotype of disease can help with design of better clinical trials and improve treatments for these patients. One of the pathways often altered in advanced prostate cancer is DNA damage response (DDR), including alterations in BRCA1/2 and other homologous recombination repair (HRR) genes. Alterations in the DDR pathway are particularly prevalent in metastatic prostate cancer. In this review, we summarise the prevalence of DDR alterations in primary and advanced prostate cancer and discuss the impact of alterations in the DDR pathway on aggressive disease phenotype, prognosis and the association of germline pathogenic alterations in DDR genes with risk of developing prostate cancer.